Biological weapons still a relevant threat - Abramson, Alfred F. III (USAWC strategy research project, 2012)
National Strategic documents address the need to counter the risks associated with Weapons of Mass Destruction (WMD). The developments and resourcing of these strategies are arguably equally divided across the spectrum of agents associated within the WMD construct. The common agents contained in that construct are the nuclear agents, chemical agents, and biological agents. Further analysis determines that, of these agents, the one that causes the most concern, and represents the greatest threat, is biological. This determination is based on the availability of biological agents to our likeliest foes, and the difficulty in rapidly detecting and accurately identifying the agent. This delay will directly affect the ability to manage contaminated areas, and effectively execute consequence management procedures to mitigate the exposure. A national response must take into account the probable limited nature of an attack, the need to coordinate among informed responders while addressing the possibility of public panic, maintaining a technological lead in sensor development, and ensuring effective cross-agency coordination at all levels of government